Biochemical and Transcriptomic Analyses Reveal Key Salinity and Alkalinity Stress Response and Tolerance Pathways in Salix linearistipularis Inoculated with Trichoderma - Zhouqing Han; Lili Chen; Wenyi Wang; Xueting Guan; Junjie Song; Shurong Ma (Agronomy)
Soil salinization and alkalinization are pervasive environmental issues that severely restrict plant growth and crop yield. Utilizing plant growth-promoting rhizobacteria (PGPR) is an effective strategy to enhance plant tolerance to saline–alkaline stress, though the regulatory mechanisms remain unclear. This study employed biochemical and RNA-Seq methods to uncover the critical growth-promoting effects of Trichoderma spp. on Salix linearistipularis under saline–alkaline stress. The results showed that, during saline–alkaline stress, inoculation with Trichoderma sp. M4 and M5 significantly increased the proline and soluble sugar contents in Salix linearistipularis, enhanced the activities of SOD, POD, CAT, and APX, and reduced lipid peroxidation levels, with M4 exhibiting more pronounced effects than M5. RNA-Seq analysis of revealed that 11,051 genes were upregulated after Trichoderma sp. M4 inoculation under stress conditions, with 3532 genes primarily involved in carbon metabolism, amino acid biosynthesis, and oxidative phosphorylation—processes that alleviate saline–alkaline stress. Additionally, 7519 genes were uniquely upregulated by M4 under stress, mainly enriched in secondary metabolite biosynthesis, amino acid metabolism, cyanamide metabolism, and phenylpropanoid biosynthesis. M4 mitigates saline–alkaline stress-induced damage in Salix linearistipularis seedlings by reducing oxidative damage, enhancing organic acid and amino acid metabolism, and activating phenylpropanoid biosynthesis pathways to eliminate harmful ROS. This enhances the seedlings’ tolerance to saline–alkaline stress, providing a basis for studying fungi–plant interactions under such conditions.